2009
DOI: 10.1590/s1516-35982009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Digestão dos carboidratos de alimentos volumosos em eqüinos

Abstract: Neste estudo, foram realizados dois ensaios com os objetivos de avaliar o fracionamento dos carboidratos de alimentos volumosos e estimar a digestibilidade desses nutrientes em dois ensaios de digestão com eqüinos. No ensaio 1, foram utilizados cinco eqüinos em delineamento de blocos casualizados, com sete tratamentos - fenos de alfafa (Medicago sativa); amendoim forrageiro (Arachis pintoi); desmódio (Desmodium ovalifolium); guandu (Cajanus cajan); macrotiloma (Macrotyloma axillare); estilosantes (Stylosanthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
4
6
1
8
Order By: Relevance
“…These constituents were also partially responsible for high 'c' degradation rate in the DM of 10.36, 20.26 and 14.8%h -1 , respectively, because the bacteria rapidly degraded them. In this case, the lucerne hay 'c' parameter was high at 13.8%h -1 , although it presented 5.2% of rapidly fermentable carbohydrates (Morgado et al, 2009), indicating that not only the rapidly fermentable carbohydrates determined the degradation rate.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…These constituents were also partially responsible for high 'c' degradation rate in the DM of 10.36, 20.26 and 14.8%h -1 , respectively, because the bacteria rapidly degraded them. In this case, the lucerne hay 'c' parameter was high at 13.8%h -1 , although it presented 5.2% of rapidly fermentable carbohydrates (Morgado et al, 2009), indicating that not only the rapidly fermentable carbohydrates determined the degradation rate.…”
Section: Resultsmentioning
confidence: 76%
“…According to Morgado et al (2009), carbohydrates breakdown in the roughages showed high amount of carbohydrates that were rapidly fermentable in the legume composition: peanut, lime yellow pea and stylo with respectively 20, 28.6 and 21% in dry matter. These constituents were also partially responsible for high 'c' degradation rate in the DM of 10.36, 20.26 and 14.8%h -1 , respectively, because the bacteria rapidly degraded them.…”
Section: Resultsmentioning
confidence: 99%
“…The protein values during the booting (164.7 g/kg DM) were higher compared to pre-flowering (149.1 g/kg DM) stage. These values are as high as the values observed in some tropical legumes like, Stylosanthes guianensis (162.0 g/kg DM [21]), Arachis pintoi(180.0 g/kg DM [22]) Gliricidia sepium (139.0 g/kg DM [22]) and are higher than those observed for most tropical grasses like, Urochloa brizantha (69.0 g/kg DM [23])and Urochloa decumbens (63.0 g/kg DM [24]). In addition, the NDF (498.0 g/kg DM) are lower than common values observed for the traditional forages (e.g.…”
Section: Introductionmentioning
confidence: 52%
“…Além disso, a fibra influencia a motilidade do alimento no trato digestório, altera a velocidade de passagem do alimento, reduz a digestibilidade dos nutrientes, aumenta a viscosidade da digesta e, consequentemente, reduz o desempenho dos animais (Meurer & Hayashi, 2003). O aumento da viscosidade intestinal diminui o contato entre as enzimas digestivas e o substrato, aumenta as perdas endógenas de nutrientes e diminui a capacidade de absorção da mucosa, o que provoca menor eficiência na digestão e absorção de nutrientes (Meurer & Hayashi, 2003;Morgado et al, 2009). Pedron et al (2008), estudaram fontes e níveis de fibra na alimentação de jundiá, e constataram que dietas com 10% de fibra bruta prejudicam a digestibilidade da proteína para a espécie.…”
Section: Resultsunclassified
“…O teor de carboidratos não fibrosos diminuiu de 6,36 para 0,23%. Estes compostos incluem amido, oligossacarídeos, frutosanas, pectinas, galactanos e β-glucanos (Morgado et al, 2009), que podem atrapalhar o aproveitamento do alimento pelo aumento da viscosidade intestinal. A redução de teor de carboidratos não fibrosos pode ter contribuído para o melhor aproveitamento de outras frações do ingrediente, como gordura e minerais.…”
Section: Resultsunclassified